Access to Justice and the Global Clinical Movement - Frank S. Bloch (Washington University Journal of Law & Policy, 2008)
This Essay takes up the question of clinical legal education’s commitment to access to justice from a global perspective and argues that an emerging global clinical movement can strengthen that commitment and increase the level and quality of law-school-based access-to-justice activity worldwide. This Essay consists of four main parts, the first three of which focus on the three key components of a global clinical movement: its global reach, its clinical base, and its status as a movement. Each of these three components is critical to the development of a global clinical movement and to its ultimate success—both generally and in its efforts to improve access to justice. Moreover, each must support and reinforce the others. Therefore, each of the next three parts of this Essay first examines one of these key components in the context of the other two and then addresses the importance of that particular component to a global clinical movement that seeks to improve access to justice around the world. The last part of the Essay suggests an approach for mobilizing the global clinical movement to improve access to justice around the world, drawing on the experience of the Global Alliance for Justice Education (“GAJE”).
Keywords: Clinical legal education; Social justice; Access to justice; Globalization – Legal Aspects; Global Alliance for Justice Education (GAJE); International